Studi Komparatif Pengaturan Tindak Pidana Revenge Porn Berdasarkan Peraturan Perundang-Undangan di Indonesia dan di Australia (Deposisi: Jurnal Publikasi Ilmu Hukum, 2024)
This study aims to determine the comparison of the regulation of revenge porn based on legislation in Indonesia and Australia. This research is a normative or doctrinal legal research with a statutory approach. The type of data used is secondary data. The technique used in collecting legal materials in this research is literature study or document study. This research uses legal reasoning analysis techniques that are sociological in nature through deductive thinking patterns, namely by explaining a general thing to then be drawn to a more specific conclusion. Based on this research, it is found that the two countries have differences in handling revenge porn cases. In Indonesia, the regulation of revenge porn is regulated in several laws, namely the ITE Law, the TPKS Law, and the Pornography Law. Unfortunately, these three regulations do not regulate revenge porn clearly and completely. Meanwhile, in Australia, there are special regulations governing online-based sexual violence crimes, including revenge porn. The regulation of revenge porn in Australia has been explained completely and comprehensively by the establishment of a complaint portal that can be accessed online by victims called eSafety Commissioner.